Association of body weight with efficacy and safety outcomes in phase III randomized controlled trials of direct oral anticoagulants: a systematic review and meta‐analysis. (9th May 2017) - Boonyawat, K.; Caron, F.; Li, A.; Chai‐Adisaksopha, C.; Lim, W.; Iorio, A.; Lopes, R. D.; Garcia, D.; Crowther, M. A.
Abstract : Essentials The association of body weight and patient‐important outcomes remains unknown. Phase III randomized controlled trials of direct oral anticoagulants (DOACs) were searched. Risk of outcomes varying among body weight subgroups is not attributable to anticoagulant type. Dose adjustment of DOACs, outside that recommended, is unlikely to improve the outcomes. Click to hear Dr Braunwald's perspective on antithrombotic therapy in cardiovascular disease Summary: Background: Concerns have arisen in direct oral anticoagulant (DOAC)‐treated patients about safety and efficacy in extremes of body weight. The aims of this systematic review were to investigate the association of body weight and patient‐important outcomes in patients treated with DOACs or warfarin, and to demonstrate the fixed‐dose effect of DOACs. Methods: MEDLINE and EMBASE were searched until November 2016. Phase III randomized controlled trials (RCTs) using DOACs in atrial fibrillation (AF) and acute venous thromboembolism (VTE) were included. Relative risk and 95% confidence interval were calculated. The pooled estimates were performed using a Mantel–Haenszel random effects model. Results: A total of 11 phase III RCTs were included. Low body weight was associated with increased risk of thromboembolism compared with non‐low body weight (relative risk [RR], 1.57; 95% confidence interval [CI], 1.34–1.85). High body weight was not associated with risk of thromboembolism compared with non‐high body weight (RR, 0.88; 95% CI, 0.63–1.23). The subgroup of AF patients with high body weight had a lower risk of thromboembolism compared with non‐high body weight (RR, 0.43; 95% CI, 0.28–0.67). Bleeding outcomes were comparable for all body weight comparisons. There were no clear interactions between types of anticoagulant in all outcomes. Conclusion: The pooled effect of both the DOAC and comparison arms was likely to be attributable to differences in baseline thrombotic risk in each body weight category, rather than an effect of the type or dose of DOAC used for each indication. Dose adjustment of DOACs, outside that recommended in the package insert, is unlikely to improve safety or efficacy.